2011
DOI: 10.1186/1755-1536-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1 in hypoxia-conditioned media blocks the growth of human microvascular endothelial cells and is increased in systemic sclerosis tissues

Abstract: BackgroundSystemic sclerosis (SSc) is a chronic inflammatory autoimmune disease characterised by vascular dysfunction and damage, excess collagen deposition and subsequent organ manifestations. Vasculopathy is an early feature of the disease which leads to a chronic hypoxic environment in the tissues. Paradoxically, there is a lack of angiogenesis. We hypothesised that this may in part be due to a nonphysiological, overriding upregulation in antiangiogenic factors produced by the hypoxic tissues. We considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Accordingly, TSP-1 upregulated in the extensively hypertrophied cardiomyocytes of SDT rat LVs at 16 wk could both induce capillary endothelial cell apoptosis and suppress capillary endothelial cell proliferation via the inhibition of VEGFstimulated VEGFR2 phosphorylation and thereby overcome the stimulatory effect of VEGF on coronary angiogenesis, leading to coronary capillary loss. These findings are compatible with those in a recent study (28) showing that in cultured human microvascular endothelial cells, despite the induction of VEGF in hypoxia-conditioned media, the increased levels of TSP-1 were able to override the protective effects of VEGF on their survival and proliferation. Taking these previous reports together with our findings, the signals from the hypertrophied cardiomyocytes under chronic hypoxia to inhibit coronary angiogenesis differ markedly between the above-mentioned models (37,45) and our own, and we suggest an important role for TSP-1 as an antiangiogenic factor in the diabetic heart of SDT rats.…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, TSP-1 upregulated in the extensively hypertrophied cardiomyocytes of SDT rat LVs at 16 wk could both induce capillary endothelial cell apoptosis and suppress capillary endothelial cell proliferation via the inhibition of VEGFstimulated VEGFR2 phosphorylation and thereby overcome the stimulatory effect of VEGF on coronary angiogenesis, leading to coronary capillary loss. These findings are compatible with those in a recent study (28) showing that in cultured human microvascular endothelial cells, despite the induction of VEGF in hypoxia-conditioned media, the increased levels of TSP-1 were able to override the protective effects of VEGF on their survival and proliferation. Taking these previous reports together with our findings, the signals from the hypertrophied cardiomyocytes under chronic hypoxia to inhibit coronary angiogenesis differ markedly between the above-mentioned models (37,45) and our own, and we suggest an important role for TSP-1 as an antiangiogenic factor in the diabetic heart of SDT rats.…”
Section: Discussionsupporting
confidence: 82%
“…Loss of cutaneous blood flow, associated tissue necrosis and poor wound healing are known consequences of age and certain vasculopathies 27,28,45 . We have reported that skeletal muscle blood flow is maintained in old TSP1- and CD47-null mice compared to old wild type animals 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The secreted matricellular protein thrombospondin-1 (TSP1) is unregulated in several disease states that are associated with loss of SkBF and impaired wound healing including diabetes, scleroderma 27 and systemic sclerosis 28 , and has recently been postulated to account for the loss of cutaneous blood flow in these individuals 29 . In pre-clinical models of cutaneous wound healing TSP1 antisense oligomers delayed wound healing 30 and overexpression of TSP1 in the skin of mice greatly slowed wound closure and wound-associated angiogenesis 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In normal physiological circumstances, tissue hypoxia and angiogenic drive attempt to recover tissue perfusion and endothelial cell function. In SSc patients, the structural changes in the microvessels are irreversible culminating in the loss of capillaries with paradoxical absence of angiogenesis [55]. The imbalance between pro-angiogenic (e.g.…”
Section: Key Immunological Mediators In Ssc-cytokines and Growth Factorsmentioning
confidence: 99%